2021
DOI: 10.1016/j.ajogmf.2020.100256
|View full text |Cite
|
Sign up to set email alerts
|

Management of brain tumors presenting in pregnancy: a case series and systematic review

Abstract: Patients who present with brain tumors during pregnancy require unique imaging and neurosurgical, obstetrical, and anesthetic considerations. Here, we review the literature and discuss the management of patients who present with brain tumors during pregnancy. Between 2009 and 2019, 9 patients were diagnosed at our institution with brain tumors during pregnancy. Clinical information was extracted from the electronic medical records. The median age at presentation was 29 years (range, 25e38 years). The most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 60 publications
2
25
0
2
Order By: Relevance
“…This may be related to the fact that meningiomas are known to express progesterone receptors, which lead to increased symptom severity during pregnancy [41]. The histological types of brain tumors are diverse [38], and in this study, we found a great variety of histological types not necessarily specific to pregnancy, which is in accordance with previous reports [37,42].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This may be related to the fact that meningiomas are known to express progesterone receptors, which lead to increased symptom severity during pregnancy [41]. The histological types of brain tumors are diverse [38], and in this study, we found a great variety of histological types not necessarily specific to pregnancy, which is in accordance with previous reports [37,42].…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the mode of delivery, cesarean section was selected in most patients, which is consistent with previous reports [37]. Cesarean section is an option to avoid increased intracranial pressure due to vaginal delivery [39].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…And there are no extracranial tumors that are likely to metastasize that are uniquely related to the specific pregnancy (5). But certain factors such as immunological tolerance, hormone-mediated growth, and hemodynamic changes may promote neoplasm growth mediating a common pathway to increasing intracranial mass effect (3,4,6). Intracranial tumors usually initially present with symptoms and signs of increased intracranial pressure such as headache, dizziness, or vomiting, related focal neurological deficits and seizures, which are often confused with pregnancy itself, hypertensive disorders and thrombosis in pregnancy (7).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with benign brain tumors, craniotomy can be performed after full-term production according to the situation. For patients with middle and late stage and large brain tumors, immediate craniotomy is recommended to reduce intracranial pressure [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%